Does Simple Steatosis Affect Liver Regeneration after Partial Hepatectomy in Rats? - Garnol, Tomáš; Kučera, Otto; Staňková, Pavla; Lotková, Halka; Červinková, Zuzana (Acta medica (Hradec Kralove), 2016)
AIM: The aim of our study was to assess whether simple steatosis impairs liver regeneration after partial hepatectomy (PHx) in rats. METHODS: Male Sprague-Dawley rats were fed a standard diet (ST-1, 10% kcal fat) and high-fat diet (HFD, 71% kcal fat) for 6 weeks. Then the rats were submitted to 2/3 PHx and animals were sacrificed 24, 48 or 72 h after PHx. Serum biochemistry, respiration of mitochondria in liver homogenate, hepatic oxidative stress markers, selected cytokines and DNA content were measured, and histopathological samples were prepared. Liver regeneration was evaluated by incorporation of bromodeoxyuridine (BrdU) to hepatocyte DNA. RESULTS: HFD induced simple microvesicular liver steatosis. PHx caused elevation of serum markers of liver injury in both groups; however, an increase in these parameters was delayed in HFD group. Hepatic content of reduced glutathione was significantly increased in both groups after PHx. There were no significant changes in activities of respiratory complexes I and II (state 3). Relative and absolute liver weights, total DNA content, and DNA synthesis exerted very similar changes in both ST-1 and HFD groups after PHx. CONCLUSION: PHx-induced regeneration of the rat liver with simple steatosis was not significantly affected when compared to the lean liver.
Keywords: Liver regeneration; krysa rodu Rattus; mužské pohlaví; Fatty liver; Partial hepatectomy; Male; jaterní mitochondrie; regenerace jater; Liver Regeneration; hepatektomie; Fatty Liver; Rats; jaterní testy; játra; Mitochondria, Liver; Animals; zvířata; ztučnělá játra; Liver; Rats, Sprague-Dawley; Liver Function Tests; potkani Sprague-Dawley; Hepatectomy